The Hobbit - "Tolkien, J.R.R" (Maqbool books: Lahore, 2012)
This official tie-in photo guidebook is packed with exclusive photographs and in-depth text offering a sneak peek at the highly anticipated new film The Hobbit: An Unexpected Journey, directed by Peter Jackson. Join the hobbit, Bilbo Baggins, Gandalf the wizard and the Company of Dwarves on their Quest to recover treasure stolen by the Dragon, Smaug the Magnificent. Leaving the comfort of Bilbo's home they must face many perils before they can claim their long-lost gold - Trolls, Elves, Goblins, Wargs, and worse ... Richly illustrated with more than 100 colour photos from the film, and featuring a brand new fold-out map charting the journey from Bag End to Wilderland, The Hobbit: An Unexpected Journey Visual Companion begins the Quest for the Lonely Mountain in spectacular style
Keywords: English Fiction